2004
DOI: 10.1002/ijc.20317
|View full text |Cite
|
Sign up to set email alerts
|

Neoexpression of N‐cadherin in E‐cadherin positive colon cancers

Abstract: In our study, we aimed to investigate the expression of N-cadherin and E-cadherin and their dependency on epithelial-mesenchymal transition regulators SNAI1, SIP1 and TWIST in human colon cancer. Expression of E-cadherin and N-cadherin was examined by immunohistochemistry in 80 colon carcinomas by using paraffin embedded and formalin fixed tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 58 publications
3
49
3
3
Order By: Relevance
“…Thus, a subset of tumors shows de novo expression or up-regulation of N-cadherin concomitant to their invasive stage. This phenomenon has been reported in melanoma (33), breast (20), prostate (24), pancreas (34), colon (35), squamous cell carcinoma (36), but also in bladder (27). Until now, expression of N-cadherin had been observed in a small number of transitional cell carcinoma of the bladder, but no prognostic value had been recognized (27).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, a subset of tumors shows de novo expression or up-regulation of N-cadherin concomitant to their invasive stage. This phenomenon has been reported in melanoma (33), breast (20), prostate (24), pancreas (34), colon (35), squamous cell carcinoma (36), but also in bladder (27). Until now, expression of N-cadherin had been observed in a small number of transitional cell carcinoma of the bladder, but no prognostic value had been recognized (27).…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, the sample sizes were relatively small, prohibiting subgroup analyses. Previous studies have shown correlations of increased N-cadherin/reduced E-cadherin expression with advancing stage (Rosivatz et al, 2004) and tumour grade (Bendardaf et al, 2005) in colorectal adenocarcinomas. The former was partly observed in this series, and is being addressed in ongoing studies.…”
Section: Discussionmentioning
confidence: 93%
“…The most striking finding was the presence of specific cadherin and vimentin phenotype. Specifically, normal colonic epithelium is characterised by E-cadherin expression but lack of N-cadherin and vimentin expression; adenocarcinoma is characterised by increased Ncadherin expression in a stepwise manner with advancing stage (Rosivatz et al, 2004), but minimal vimentin expression; and PMP has high expression of N-cadherin and reduced E-cadherin expression. This cadherin phenotype is suggestive of an EMT state, a process important in the progression of neoplasia towards dedifferentiation and more 'malignant' states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in some of the above-mentioned studies, the precise contribution of stromal and carcinoma cells to the expression of Sna1 was not assessed. May be owing to these reasons, other groups have been unable to detect Snail in some of these tumors (Rosivatz et al, 2004).…”
Section: Discussionmentioning
confidence: 98%